Effect of Etomidate on Pneumonia Development in Critically Ill, Nontrauma Patients. (January 2019) - Hammond, Drayton A.; Vines, Claire E.; McPhee, Ashley L.; Bhandari, Naleen Raj; Jones, Kendrea M.; Meena, Nikhil; Painter, Jacob T.
Purpose: To determine whether etomidate use before intubation increased development of hospital-acquired pneumonia (HAP) in critically ill, nontrauma patients. Materials and Methods: A single-center, retrospective, cohort study of critically ill, nontrauma patients admitted to the medical intensive care unit (ICU) from 2012 to 2015 and intubated with or without etomidate was conducted. Demographics, comorbidities, primary diagnosis, critical illness scores, concomitant medications, and outcomes were obtained from medical records. Student t, chi-square, and Fisher exact tests were performed as appropriate. Relevant characteristics were modeled using logistic regression techniques to determine whether any predicted HAP independently. Results: Of the 174 patients, 94 (54%) received etomidate and 80 (46%) did not. There was no difference in HAP between etomidate and no etomidate groups (13.8% vs 23.7%, P = .092). Duration of mechanical ventilation (4.4 vs 4.6 days, P = .845), ICU length of stay (7.4 vs 6.9 days, P = .547), ICU mortality (14.9% vs 12.5%, P = .648), and hospital mortality (17% vs 16.2%, P = .892) were similar between the groups. For each 1-day increase in mechanical ventilation duration, the likelihood of HAP development increased by 21%. Patients who received etomidate but no neuromuscular-blocking drug were 80% less likely to develop HAP than those who did not receive etomidate or a neuromuscular-blocking drug (odds ratio: 0.202, 95% confidence interval: 0.045-0.908). Conclusion: Etomidate use was not associated with a difference in HAP development in critically ill, nontrauma patients.